Efficacy & Biochemical Evaluation of Pharmaceutical Optimized Atenolol 50mg (F-9) with Essential Hypertension (Medical Forum Monthly, 2024)
Objective: The objective of this double-blind, Placebo control study evaluating efficacy and biochemical effects of optimized Atenolol 50mg (F-9) as monotherapy in adult patient with essential hypertension.Study Design: Double-blind, Placebo control study.Place and Duration of Study: This study was conducted at the Department of Biochemistry, University of Karachi from February2011 to September 2011.Materials and Methods: This was multicenter randomized, double-blind, Placebo control study. Patients were randomized to receive once Atenolol (F-9) daily for 8 weeks and at the end of study efficacy and biochemical evaluation was doneResults: The patients treated with optimized Atenolol 50mg (F-9) alone, blood pressure reduction was lower, although significant; reaching values of 140.9 ± 11.3 / m88.9 ± 5.5 mmHg (p < 0.05 versus Placebo) by the end of eight weeks of treatment. . No significant variation of blood glucose was observed and different parameters of lipid profile were also observed during the eight weeks of treatment with antihypertensive regimen used. Thus, the drug regimens used may be considered neutral as regards glucose and plasma lipid metabolism profile because drug used at low doses.Conclusion: We can suggest that the high antihypertensive efficacy, good tolerability and no biochemical effects of the optimized Atenolol50mg (F-9) it is an excellent option for the treatment of hypertension in a wide range of hypertensive patients, with a high potential to reduce cardiovascular risks.